A matrix converter drive system for an aircraft rudder electro-mechanical actuator - De Lillo, Liliana (2006)
The matrix converter is an attractive topology of power converter for the Aerospace Industry where factors such as the absence of electrolytic capacitors, the potentiality of increasing power density, reducing size and weight and good input power quality are fundamental. The matrix converter potential advantages offers the possibility to achieve the aim of the More Electric Aircraft research which intends to gradually re- place, from the aircraft architecture, the hydraulic power source and its infrastructure with electric power generation and a more flexible power distribution system.